Child rights in India - "Bajpai, Asha" (New Delhi, 2003)
This comprehensive, timely, and analytical book is a storehouse of valuable information about the state of child rights in India. In an introduction specially written for the second edition, Asha Bajpai brings the work up to date on developments since its original publication. She discusses significant changes in the law including those brought about by the Prohibition of Sex Selection Act, 2003, the directions by the Supreme Court of India for its implementation, and the Juvenile Justice (Care and Protection of Children Amendment) Act, 2005. Proposed amendments in the law including the Prevention of Child Marriage Bill, 2004, the Right to Education (Draft) Bill, 2005 and the Offences Against the Child Bill, 2006 are reviewed by her. She shows how India is moving in the direction of the standards set by inter- national law, though lacunae remain, and monitoring and enforcement remain important issues.
Keywords: Child law